2019
DOI: 10.1101/2019.12.21.886044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

XACT-seq comprehensively defines the promoter-position and promoter-sequence determinants for initial-transcription pausing

Abstract: Pausing by RNA polymerase (RNAP) during transcription elongation, in which a translocating RNAP uses a "stepping" mechanism, has been studied extensively, but pausing by RNAP during initial transcription, in which a promoter-anchored RNAP uses a "scrunching" mechanism, has not. We report a method that directly defines RNAP-active-center position relative to DNA in vivo with single-nucleotide resolution (XACT-seq;crosslink-between-active-center-and-template sequencing). We apply this method to detect and quanti… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 48 publications
1
2
0
Order By: Relevance
“…A recent study on initial transcription in vivo (15) and our results suggest that at each nucleotide addition step, ITCs harboring 3-8 nt RNAs can enter into a paused state. The paused ITC (PITC) bifurcates in two pathways: abortive pathway in which nascent RNA dissociates from RNAP, and productive pathway in which nascent RNA remains bound to RNAP and slowly translocates to the next register (Figure 7).…”
Section: Initial Transcription Pausing On the Pathway To Abortive Trasupporting
confidence: 73%
See 1 more Smart Citation
“…A recent study on initial transcription in vivo (15) and our results suggest that at each nucleotide addition step, ITCs harboring 3-8 nt RNAs can enter into a paused state. The paused ITC (PITC) bifurcates in two pathways: abortive pathway in which nascent RNA dissociates from RNAP, and productive pathway in which nascent RNA remains bound to RNAP and slowly translocates to the next register (Figure 7).…”
Section: Initial Transcription Pausing On the Pathway To Abortive Trasupporting
confidence: 73%
“…Nascent RNA chains shorter than 9 nt form unstable hybrids with ssDNA templates and tend to dissociate from the RNAP active site (2,7,11). However, short RNAs (5-6 nt in length) can be stably bound in the paused initially transcribing complex (ITC) formed at the lacUV5 promoter in vitro (12)(13)(14) and in vivo (15). The initial transcription pause occurring after the synthesis of 6-nt RNA functions as a checkpoint on the branched pathway between productive and nonproductive transcription (14).…”
Section: Introductionmentioning
confidence: 99%
“…When it occurs, pausing on the pathway to productive initiation delays transcription kinetics on a physiological timescale by affecting promoter escape [ 10 , 11 , 12 , 23 ]. It has been reported that specific sequences in ITS can induce pausing during initiation [ 21 , 24 ]. Therefore, not only the moribund complex, but also RNAP pausing of the productive complex can provide sequence-specific mechanisms controlling transcription during initiation.…”
Section: Introductionmentioning
confidence: 99%